Bridging training and practice gap: A mixed methods tracer study of bachelor of science in nursing graduates (2016–2020) at Kairuki University, Dar es Salaam, Tanzania - Adellah Sariah; Minael Nathanael; Monica Bugomola; Edson Sungwa; Mathew Ndomondo; Elizabeth Mika; Tausi Haruna; Joan Zenas; Ezekiel Mbao; Innocent Semali; Columba Mbekenga (PLoS ONE, 2025)
Background Tracer studies evaluate the effectiveness of university training by assessing how graduates perform in the job market. This study focused on Bachelor of Science in Nursing (BScN) graduates, aiming to describe their training experiences, application of acquired competencies, and overall stakeholder perceptions to inform BScN curriculum improvement. Methods A convergent parallel mixed-method design was used to collect quantitative and qualitative data concurrently from 2016–2020 BScN graduates (February-May 2023). Graduates and other stakeholders (including educators, employers, and policymakers) in this study were selected from private, public, and faith-based hospitals and universities, colleges, and the Ministry of Health. Quantitative data were gathered via online structured questionnaires adapted and modified from the American International Health Alliance and the Technical Vocational Education and Training tools. Qualitative data were collected through interviews and focus groups with graduates, employers, educators, and policymakers. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent thematic analysis. Integration occurred during interpretation to provide a comprehensive understanding of graduates’ experiences, competency application, and stakeholder perceptions of the BScN program. Results Among the 61 graduates who completed the online survey, 37 (60.7%) were female. Most (48; 78.7%) worked as nurses, while 6 (9.8%) were tutors and 3 (4.9%) worked as tutorial assistants. Demonstration was rated the most useful teaching and learning method by 52 (85.2%) respondents, and 47 (81%) rated practical exams as a useful assessment method. These were also supported by graduates and stakeholders who shared their perspectives with regard to the benefits and impact of the BScN program and training quality. Additionally, 54 graduates (94.7%) found the program very useful in preparing them for their professional roles, which aligned with their views on the connection between acquired competencies and job performance. Both graduates and educators highlighted challenges encountered during training and in professional practice. Policymakers and graduates also offered recommendations for improving the program. Additionally, 54 graduates (94.7%) found the program very useful in preparing them for their professional roles, which aligned with their views on the connection between acquired competencies and job performance. Both graduates and educators highlighted challenges encountered during training and in professional practice. Policymakers and graduates also offered recommendations for improving the program. Conclusion The findings demonstrate that the BScN program is widely regarded by graduates and stakeholders as effective in preparing students for professional practice, particularly through practical teaching methods such as demonstrations and practical exams. While the program’s impact on competency development and job performance was strongly affirmed, the study also revealed notable challenges during training and practice. These insights support the ongoing review and enhancement of the BScN curriculum.